Geographic Differentiation and Population Genetic Structure of Moniliophthora roreri in the Principal Cocoa Production Areas in Colombia - Jaimes, Yeirme Y. [UNESP]; Gonzalez, Carolina; Rojas, Jairo; Cornejo, Omar E.; Mideros, Maria F.; Restrepo, Silvia; Cilas, Christian; Furtado, E. L. [UNESP] (Amer Phytopathological Soc, 2016)
Frosty pod rot (FPR) disease on cocoa, caused by Moniliophthora roreri, is one of the most devastating cocoa disease in the Western Hemisphere. In Colombia, the disease is particularly severe in the Magdalena Valley, which is considered the possible center of origin for the pathogen species. We analyzed the genetic diversity of isolates from the departments of Santander, Antioquia, Tolima, and Huila in Colombia using 23 simple sequence repeats (SSR) markers. In total, 117 different multilocus genotypes were found among 120 isolates, each one representing a unique haplotype. High mutation rates in the SSR and gene flow can explain the high levels of diversity. Also, the observed and standardized indexes of association (I-A and rd) indicate that the populations of M. roreri are clonal. Furthermore, given the high haplotype diversity and the significant linkage disequilibrium observed, we hypothesize that M. roreri could be a primarily asexual species undergoing sporadic recombination or partial recombination through parasexuality. A Bayesian clustering analysis implemented by STRUCTURE showed that the most probable number of genetic groups in the data was three, confirming the geographical differentiation among isolates Similar results were obtained by a discriminant analysis of principal components, a principal coordinate analysis, and a neighbor-joining tree from microsatellite loci base on Nei distance. Cacao genotypes and environmental variables did contribute to the genetic differentiation of the groups. We discuss how this information could be used to improve the management of FPR at the regional level.